Petangan tradition in Javanese personal naming practice: an ethnoliguistic study - Sahid Teguh Widodo,; Kundharu Saddhono, (Penerbit UKM, 2012)
This study investigates petangan, a form of tradition which belongs to the Javanese cultural heritage. Petangan (a study of calculation) plays an important role in Javanese culture. The petangan tradition first appeared centuries ago, at which time it has been developed and recorded in both written and oral traditions. The scope of this research focuses on a study of the petangan tradition in relation to personal naming practices. This study applied a qualitative research method - elaborated in order to identify various ways in which the Javanese give meaning to, evaluate, and predict the character of the name given to their children using the petangan tradition. This tradition is very popular in Java. However, in its development, it has started to become less prevalent among the Javanese community since it must compete with many forms of counter culture which are more modern, rational and instant. Data are collected from the sources of data obtained from documents and observation. The data analysis technique employed in this research is interactive analysis technique which involved three simultaneous activities: data reduction, data presentation, and verification. To obtain the validity of data, data verification was done through data triangulation by comparing the data presented to previous researches and petangan books. The finding of the research shows that petangan has important role in Javanese naming tradition in terms of its form, use, and social function in Javanese society. This study also discovers the development of personal naming practice, ideas, cultural taste, and various other changes which are taking place in the Javanese society from one era to another.